Criminal (2006), volume 5 ebook The sinners. - Brubaker, Ed (Criminal (2006), 2015)
Tracy Lawless returns with a vengeance in this strikingly-designed new edition from Image Comics. One year after the events of CRIMINAL, VOL. 2: LAWLESS, Tracy Lawless is still a man caught between a history of violence and his own conscience. And now the worst bad guy in the world is tasked with a new job: Solving a series of murders of untouchable crime lords. CRIMINAL returns to its hard-hitting pulp roots! Author: Ed Brubaker. Illustrator: Sean Phillip, Val Staples . 2015 Basement Gang Inc.